Formulation Facial wash with Addition of Coriander Leaf Extract (Coriandrum savitum L) - Gusti Permana; Ahmad Syarbaini; Amar Ma'ruf (JURNAL AGROINDUSTRI HALAL, 2024)
Coriander leaves have functional properties such as antioxidant, antidiabetic, anticholesterol, antimicrobial, anti-inflammatory, and analgesic. Ethanol-extracted coriander leaves exhibit an antioxidant activity of 91.2287 μg/mL. The high antioxidant activity value of coriander leaf extract can be developed into a free radical scavenging product like facial wash. This research aims to determine the physicochemical characteristics of coriander leaf extract facial wash formulations at 10%, 12.5%, and 15% concentrations. Organoleptic sensory and hedonic tests, as well as physicochemical tests, were conducted. The test data were processed using SPSS and subjected to Duncan's post hoc test. The obtained data were then compared with predetermined standards. The resulting coriander leaf (Coriandrum sativum L) facial wash formulation in this study has a semi-solid texture, distinctive aroma, dark brown color, pH ranging from 6.96 to 9.24, foam stability ranging from 82.15% to 92.80%, irritation value ranging from 8.29 to 8.46, and viscosity ranging from 2436.92 cPs to 3236.38 cPs, but it lacks good homogeneity